Improving The Skills Of Counselors Using KREIN-MKP (Creative And Innovative Cognitive-Based Behavioral Counseling) To Reduce Covid-19 Pandemic Anxiety - Yeni Karneli; Yarmis Syukur; Riska Pratiwi (Jurnal Neo Konseling, 2020)
Covid-19 massif attacks have impacted the world of education, nearly 300 million students disrupted their school activities around the world and threatened their educational rights in the future.This condition will interfere with the achievement of students' maturity in achieving their learning goals, both academically, and psychologically.Students who are transferred to learning due to school closures are very likely to experience psychological trauma that makes them demotivated in learning.Schools were closed, and online learning left many students depressed.Students who are victims of the covid-19 pandemic feel they are in an uncomfortable state, panic, fear, anxiety that can ultimately make them anxious.This community service aims to help students reduce anxiety by using KREIN-MKP (Creative Counseling And Innovative Cognitive Behavioral Based), improving teacher insights BK/school counselor on covid-19 pandemic anxiety disorder that occurs in vocational school students, providing improved skills of BK teachers using KREIN-MKP (Creative and Innovative Cognitive Behavioral Based Counseling).This research uses descriptive methods through action research. The target audience in community service activities is bk teachers/counselors who serve in SMK Kota Padang.Data collection techniques are via online via google form. The results were obtained in the form of improving the skills of BK teachers/counselors in carrying out counseling with a KREIN-MKP approach that focuses on the problems experienced by students such as covid-19 pandemic anxiety disorder.